Forming Process, Pattern and the Need for Intergovernmental Management in Indonesia - Warsono, Hardi (UI Scholars Hub, 2013)
Cooperation among neighbouring region is commonly termed regional cooperation. Inter-region cooperation in the study of public administration is categorized as public management especially intergovernmental management. Inter-region cooperation in Indonesia has been for a long time trying to find its form. However, in the middle of its process, the implementer is trapped in doubt. The paper aims to trace the institutional form and its problem in the neighbouring region cooperation. The research is done through literature study, observation on inter-region cooperation especially in the central Java and some facilitation done by the writer in the several regions in Indonesia. There are two forms of referred institution which is developed on the basis of this networking pattern; they are intergovernmental relation (IGR) and intergovernmental management (IGM). In the mean time, the governmental support on inter-region cooperation which is supposed to form collaboration is hampered by the inconsistency of regulation which is issued by several parties (ministries) in the central government.